FLUIDIZED BED WET GRANULATION OF UREA USING STARCH BASED BINDER: EXPERIMENTAL AND MODELING STUDIES - RAJABI, EHSAN ZHALEH (2021)
Fluidized bed wet granulation is one of the industrial processes used to produce urea granules with a desired size using binder materials. Unlike the commercial binders, the use of biodegradable binders, besides being environmentally-friendly, also potentially offer cheaper processing cost. However, the utilization of starch based binders for urea granules is limited. To fully utilize the starch based binder, investigations on binder properties and granulation operating conditions become crucial. Furthermore, the particle size distribution and granulation kinetics are the important parameters to be studied to estimate the granulation performance and duration. In the current research, the urea powder is granulated in a wet fluidized bed granulator using starch based binder (starch and urea) solution spraying from the top of the powder bed. The urea and starch were used to synthesize the starch based binder, and the binder properties such as viscosity, surface tension, contact angle, penetration time, and liquid bridge bonding force were characterized under different concentrations of urea and starch.